Exclusionary interactions among diverse fungi infecting developing seeds of Centaurea stoebe. Issue 1 (20th December 2012) - Raghavendra, Anil Kumar H.; Newcombe, George; Shipunov, Alexey; Baynes, Melissa; Tank, David
Abstract Developing seeds are expected to be strongly defended against microbial attack. In keeping with this, only 26% of seeds of Centaurea stoebe from its native and invaded ranges in Eurasia and North America were infected with fungi, and 92.2% of those were infected with a single fungus per seed. Even when developing seeds in flower heads were inoculated under conducive conditions for infection with 14 of these seed‐infecting fungi, re‐isolation of inoculants was only 16% overall, and again limited to the particular inoculant. Environmental fungi (i.e. those not isolated from seed of C. stoebe) were present in control flower heads under conditions conducive to infection but they were never re‐isolated from fully developed seeds in any experiments. When two or three seed isolates were co‐inoculated to compete in flower heads, only one inoculant, and always the same one, was re‐isolated from all matured seeds, regardless of maternal plant genotype. PCR‐based detection methods confirmed that these fungal interactions were exclusionary rather than suppressive. In these strongly defended, developing seeds, we had expected the plant to control not only the overall level of infection but also the outcome of co‐inoculations. Consequences for the next plant generation of this exclusionary competition among seed‐infecting fungi included effects on seedling emergence, growth and fecundity.